MENINGKATNYA INTENSITAS KONFLIK DESA PAKRAMAN DI BALI - Diah Prami, Anak Agung Istri Ngurah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2014)
Abstract Balinese society are bound by two village system, they are village administration (village official) and traditional village (desa pakramaan). In practice, the two systems villages are often overlap . Thus, it is not uncommon cause of conflict in society. This condition is worsened by the full authority for Pakraman to manage its resources based on the Bali Provincial Regulation No. 3 of 2001 on Pakraman. In an effort to resolve conflicts need for conflict management in the form of deliberation to reach a deal. Keywords: conflict, traditional village.